ANALISIS KEPUASAN KONSUMEN BADAN PUSAT STATISTIK (BPS) KABUPATEN MOROWALI - Tovan Tovan (Jurnal Mirai Management, 2019)
This study aims to provide an overview and analysis of segmentation of data users and their level of satisfaction as well as recommendations on the types and quality of data and statistical information, service variables that need to be improved, anti-corruption behavior that need to be improved, as well as follow-up actions on research results. The scientific approach used is quantitative research and qualitative research with the method of index analysis, percentage, and gap analysis. Respondents in this study were BPS data users during the past 1 (one) year as many as 40 respondents with representation from government agencies, private sector, educational institutions, and others. Preferred data collection through face-to-face interviews or direct visits using a questionnaire. The results of the study found that in general consumers or customers of BPS Morowali were already in a condition that was satisfied with the service, and the quality of data and anti-corruption behavior in the BPS Morowali environment. Keywords: Satisfaction, Service, and Anti-Corruption Behavior